Strategies to address diabetic kidney disease burden in Mexico: a narrative review by the Mexican College of Nephrologists - Palomo-Piñón, Silvia; Aguilar-Alonso, Jesús Armando; Chávez-Iñiguez, Jonathan Samuel; Hernández-Arellanes, Felipe Ericel; Mariano-Murga, Jesús Antonio; Flores-Rodríguez, Juan Carlos; Pérez-López, María Juana; Pazos-Pérez, Fabiola; Treviño-Becerra, Alejandro; Guillen-Graf, Aurora E.; Ramos-Gordillo, Jesús Manolo; Trinidad-Ramos, Pedro; et al. (Frontiers in Medicine, 2024)
Chronic kidney disease (CKD) is a growing global public health challenge worldwide. In Mexico, CKD prevalence is alarmingly high and remains a leading cause of morbidity and mortality. Diabetic kidney disease (DKD), a severe complication of diabetes, is a leading determinant of CKD. The escalating diabetes prevalence and the complex regional landscape in Mexico underscore the pressing need for tailored strategies to reduce the burden of CKD. This narrative review, endorsed by the Mexican College of Nephrologists, aims to provide a brief overview and specific strategies for healthcare providers regarding preventing, screening, and treating CKD in patients living with diabetes in all care settings. The key topics covered in this review include the main cardiometabolic contributors of DKD (overweight/obesity, hyperglycemia, arterial hypertension, and dyslipidemia), the identification of kidney-related damage markers, and the benefit of novel pharmacological approaches based on Sodium-Glucose Co-Transporter-2 Inhibitors (SGLT2i) and Glucagon-Like Peptide-1 Receptor Agonists (GLP-1 RA). We also address the potential use of novel therapies based on Mineralocorticoid Receptor Antagonists (MRAs) and their future implications. Emphasizing the importance of multidisciplinary treatment, this narrative review aims to promote strategies that may be useful to alleviate the burden of DKD and its associated complications. It underscores the critical role of healthcare providers and advocates for collaborative efforts to enhance the quality of life for millions of patients affected by DKD.